Psychometric evaluation of the 11-item English language usage scale in commencing nursing students. (January 2021) - Salamonson, Yenna; Glew, Paul J.; Ramjan, Lucie M.; Jefferies, Diana; Maneze, Della; Crook, Benjamin; Everett, Bronwyn
Abstract: Background: Globalisation has increased the number of students from culturally and linguistically diverse backgrounds enrolling in nursing programs where English is the primary medium of instruction. These students may experience challenges with English language usage and need to be identified early to ensure academic success. Objective: To develop and test the psychometric properties of a self-report English language usage scale (ELUS-11). Methods: Prospective, correlational study of commencing nursing students enrolled in a communication unit at a university in the western Sydney region of Australia. English-language usage was measured using the ELUS-11, an 11-item self-report tool with a 5-point Likert scale response format. Factorial validity was examined using exploratory and confirmatory factor analysis and logistic regression was used to compute the predictive validity of the ELUS. Results: Of the 1723 students enrolled, 1100 (64%) returned surveys with all items of the ELUS-11 completed. The mean age of respondents was 25.4 years ( SD : 8.0 years), 85% were female and 67% spoke a language other than English at home. Exploratory factor analysis yielded a one-factor structure that explained 65% of the variance, with factor loadings ranging from 0.72 to 0.86; and high internal consistency ( α = 0.96). The ELUS-11 was able to discriminate among different groups of students based on age, domestic/international enrolment status and language spoken at home (all p < 0.001). Logistic regression revealed the ELUS-11 had good predictive validity, with those in the high ELUS-11 group over three times more likely to obtain a pass grade in their first written assessment (Adjusted odds ratio: 3.01, 95% CI: 2.05–4.43). Conclusion: The ELUS-11 is a valid and reliable measure of English-language usage, and appropriate for use in an undergraduate nursing population to identify students at risk of poor academic performance.